DETERMINATION OF COMPENSATION BASED ON LAW NUMBER 2 OF 2012 ARTICLE 9 PARAGRAPH 2 - Effendry (Bhayangkara Law Review, 2024)
To ensure that development is carried out for the public interest, the government must carry out development. Therefore, the values ​​of humanity, democracy and justice must be prioritized in land acquisition. To realize a just, prosperous and prosperous society based on Pancasila and the 1945 Constitution of the Republic of Indonesia, this is necessary. The Public Appraisal Service Office (KJPP), which estimates a fair replacement value for community assets (land and buildings) damaged by development, is one of the professions involved in the implementation of land purchases. Law Number 2 of 2012, which regulates the purchase of land for development in the public interest, regulates participation. Compared to ten years ago, Indonesia is now doing a lot more appraisal work. The difficulty of reaching an agreement between the party needing the property (the land acquisition party) and the land owner on the amount of compensation to be received by the land owner is a problem that often arises in the process of determining compensation in land acquisition. Landowners were compensated in ways deemed inappropriate and unfair, and which did not promote the welfare of the environment, leading to legal problems (lawsuits).The normative juridical method with a literature study approach was chosen as the research methodology in this study. The literature study method gathers information from a variety of literary sources, including books, scientific journals, laws and regulations, decision studies, and other materials relevant to the research topic. The purpose of this descriptive research is to describe and explain phenomena related to the research topic.Based on research findings, the calculation of compensation that is correct and fair in land acquisition is necessary for the welfare and prosperity of the people. Law Number 2 of 2012 concerning Land Acquisition for Development in the Public Interest which regulates land acquisition for public purposes has been in effect. Comprehensive and applicable laws and regulations play an important role in this land acquisition, procedures that are as simple as possible, transparent, and have legal certainty based on the principles of integrity and fairness are also important. The government needs to find a solution that can minimize the negative impact on the people whose land is being taken, while maximizing the positive impact on the wider community. The Public Appraiser Service Office must raise the status of the Appraiser Bill so that it is immediately passed into the Appraisal Act by the DPR so that it can carry out its professional responsibilities with legal certainty and without being criminalized by other parties.